Social Parameters in the Genre of Communicative Simulation - Olga V. Zaytseva; Pavel A. Katyshev (Виртуальная коммуникация и социальные сети, 2023)
Communicative simulation is a virtual practice that reproduces offline forms of social interaction using information and communication technologies. This research parametrized communicative simulation genres and described the interpersonal aspect of virtual interaction in a virtual environment, i.e., bricolage form, intersemiotics, and reduced corporality. Communicative simulations differ from such social practices as offline simulations or role games. The social aspect of communicative simulations includes (1) the media nature of virtual interaction; (2) the hybrid nature of communicative simulations that combines the features of both ordinary simulations and text-based role games; (3) the dual nature of social interaction, carried out simultaneously in material and diegetic spaces. As a result, the social aspect of communicative simulation can be presented in the form of a three-level model: material, diegeological, instrumental levels.